U.S. presence and the incidence of conflict - O'Mahony, Angela (RAND, 2018)
"There is an ongoing debate about the effects of U.S. military presence on conflict around the globe. In one view, U.S. military presence helps to deter adversaries, restrain U.S. partners from adopting provocative policies, and make it easier for the United States to achieve its aims without the use of force. In another view, U.S. military presence tends to provoke adversaries and encourage allies to adopt more reckless policies, and it increases the likelihood that the United States will be involved in combat. The authors of this report analyze historical data to assess how U.S. military presence -- in particular, U.S. troop presence and military assistance -- is associated with the interstate and intrastate conflict behavior of states and nonstate actors. Troop presence and military assistance have different effects. Stationing U.S. troops abroad may help deter interstate war. A large U.S. regional troop presence may reduce the likelihood of interstate conflict in two ways: by deterring potential U.S. adversaries from initiating interstate wars or by restraining U.S. allies from initiating militarized behavior. However, U.S. military presence may increase interstate militarized activities short of war. U.S. adversaries may be more likely to initiate militarized disputes against states with a larger U.S. in-country troop presence. U.S. troop presence does not appear to reduce the risk of intrastate conflict or affect the level of state repression. U.S. military assistance is not associated with changes in interstate conflict behavior. However, provision of U.S. military assistance may be associated with increased state repression and incidence of civil war. These findings have implications for near-term decisionmaking on U.S. forward troop presence in Europe and Asia."--Publisher's description
"Prepared for the United States Army"--Title page
"This research was sponsored by the Deputy Chief of Staff, G-2, United States Army..."--RAND website
Keywords: USA -- Army; Krieg; Unterstützung; USA; Military assistance, American / Foreign countries; United States / Armed Forces / Foreign countries; War / Causes; War / Forecasting; Armed Forces; United States